Festschrift Heinz Luschey
ersch. 1986; S. 7: Widmung, W. Kleiss, P. Calmeyer ; S. 9-11: Worte freundlichen Geleites, W. Hinz ; S. 13: Ergänzungen zur Bibliographie von Heinz Luschey (AMI 8, 1975, 9 f.).